Arg-85 and Thr-430 in murine 5-aminolevulinate synthase coordinate acyl-CoA-binding and contribute to substrate specificity - Lendrihas, Thomas (Wiley Subscription Services, Inc., A Wiley Company, 2009)
5-Aminolevulinate synthase (ALAS) controls the rate-limiting step of heme biosynthesis in mammals by catalyzing the condensation of succinyl-coenzyme A and glycine to produce 5-aminolevulinate, coenzyme-A (CoA), and carbon dioxide. ALAS is a member of the α-oxoamine synthase family of pyridoxal 5′-phosphate (PLP)-dependent enzymes and shares high degree of structural similarity and reaction mechanism with the other members of the family. The X-ray crystal structure of ALAS from Rhodobacter capsulatus reveals that the alkanoate component of succinyl-CoA is coordinated by a conserved arginine and a threonine. The functions of the corresponding acyl-CoA-binding residues in murine erthyroid ALAS (R85 and T430) in relation to acyl-CoA binding and substrate discrimination were examined using site-directed mutagenesis and a series of CoA-derivatives. The catalytic efficiency of the R85L variant with octanoyl-CoA was 66-fold higher than that of the wild-type protein, supporting the proposal of this residue as key in discriminating substrate binding. Substitution of the acyl-CoA-binding residues with hydrophobic amino acids caused a ligand-induced negative dichroic band at 420 nm in the CD spectra, suggesting that these residues affect substrate-mediated changes to the PLP microenvironment. Transient kinetic analyses of the R85K variant-catalyzed reactions confirm that this substitution decreases microscopic rates associated with formation and decay of a key reaction intermediate and show that the nature of the acyl-CoA tail seriously affect product binding. These results show that the bifurcate interaction of the carboxylate moiety of succinyl-CoA with R85 and T430 is an important determinant in ALAS function and may play a role in substrate specificity.